(E,E)-1,2-Bis[4-(prop-2-yn-1-yloxy)benzylidene]hydrazine - Al-Mehana, Wisam Naji Atiyah; Yahya, Rosiyah; Lo, Kong Mun (International Union of Crystallography, 2011)
The mol-ecule of the title compound, C(20)H(16)N(2)O(2), is centrosymmetric with the mid-point of the central N-N bond located on an inversion center. The configuration around the C=N bond is E. The whole mol-ecule (except for the H atoms) is approximately planar, with an r.m.s. deviation of 0.07 Å. In the crystal, the presence of weak inter-molecular C-H⋯O hydrogen bonding involving each acetyl-ene H atom and the adjacent phen-oxy O atom results in the formation of supra-molecular chains.